Youth Voting, Rational Competency, and Epistemic Injustice - Baumtrog, Michael D. (Informal Logic, 2021)
In 1970 the voting age in Canada changed from 21 to 18. Since then, there have been calls to lower it further, most commonly to age 16. Against the motion, however, it has been argued that youth may lack the ability to exercise a mature and informed vote. This paper argues against that worry and shows how restricting youth from voting on the basis of a misbelief about their abilities amounts to an epistemic injustice.